2021
DOI: 10.1021/acsestwater.0c00267
|View full text |Cite
|
Sign up to set email alerts
|

Unaccounted Microplastics in Wastewater Sludge: Where Do They Go?

Abstract: Wastewater treatment plants (WWTPs) could reintroduce microplastics into environments via biosolid application on land. Yet, the annual emission of microplastics via wastewater biosolids is unclear. Analyzing results from 76 studies, we estimate median concentrations of microplastics in influent, effluent, and sludge in various regions in the world and found that only 4% of microplastics removed in WWTPs are detected in the biosolids, and the remaining 96% could be unaccounted for. Unaccounted microplastics ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 151 publications
0
36
0
2
Order By: Relevance
“…Microplastics <100 μm in size are often unretained by sampling and preparation techniques . The small size of microplastics and the complexity of wastewater-related matrices complicate accurate identification and quantification of microplastics. , Polymer types beyond the “usual suspects” (i.e., polyethylene, polypropylene, PET, PS, and polyvinyl chloride) often go unquantified. Understudied polymer classes include paint/coating-associated urethanes, acrylates, and butadiene-based rubbers common in tire wear. ,,, These may be toxicologically relevant (e.g., the tire antioxidant additive degradant described previously) .…”
Section: Methods For Sampling and Quantifying Microplastics In Wwtp M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics <100 μm in size are often unretained by sampling and preparation techniques . The small size of microplastics and the complexity of wastewater-related matrices complicate accurate identification and quantification of microplastics. , Polymer types beyond the “usual suspects” (i.e., polyethylene, polypropylene, PET, PS, and polyvinyl chloride) often go unquantified. Understudied polymer classes include paint/coating-associated urethanes, acrylates, and butadiene-based rubbers common in tire wear. ,,, These may be toxicologically relevant (e.g., the tire antioxidant additive degradant described previously) .…”
Section: Methods For Sampling and Quantifying Microplastics In Wwtp M...mentioning
confidence: 99%
“…Thus, consideration of the larger numbers and particle sizes (masses) of microplastics suggests that their contributions in sludges are underestimated. Koutnik et al postulated that 96% of the microplastics in wastewater sludge may go undetected due to methodological shortcomings . Once therein, stabilization practices, land application, and later environmental processes will fragment these into ever greater numbers of smaller particles, including nanoplastics.…”
Section: Wastewater Treatment Solidsmentioning
confidence: 99%
“…Insbesondere landwirtschaftliche Böden werden durch zusätzliche Eintragsquellen belastet. Kompost oder Klärschlamm, die als wichtige Düngemittel aufgetragen werden, enthalten bereits erhebliche Mengen an Mikro-und Nanoplastik mit bis zu 300 000 Partikeln in einem kg Klärschlamm [1]. Zudem ist es gängige Praxis, Mulchfolien auf landwirtschaftlichen Feldern zur Ertragssteigerung zu nutzen.…”
Section: Introductionunclassified
“…Given the growing awareness and concern over microplastics pollution, studies are now appropriately focused on developing methods that prevent their broader release into the environment. , Wastewater treatment plants are a key location for such prevention. Recent studies have shown that these plants efficiently capture microplastics within nutrient-rich biosolid waste during coagulation and settling. Unfortunately, this sludge is often sold as fertilizer, thereby releasing the captured microplastics into the environment. , As a result, methods that remove microplastics upstream of sludge formation are needed . One emerging technology aimed at removing microplastics earlier in the treatment process involves using magnets to separate magnetic materials that adsorb microplastics, including nanotubes, coagulants, nanoparticles, and core–shell particles .…”
Section: Introductionmentioning
confidence: 99%
“…26−28 Unfortunately, this sludge is often sold as fertilizer, thereby releasing the captured microplastics into the environment. 29,30 As a result, methods that remove microplastics upstream of sludge formation are needed. 24 One emerging technology aimed at removing microplastics earlier in the treatment process involves using magnets to separate magnetic materials that adsorb microplastics, including nanotubes, 31 coagulants, 32 nanoparticles, 33 and core−shell particles.…”
Section: ■ Introductionmentioning
confidence: 99%